Diagnostic accuracy of sacral rhomboid dimensions in prediction of cephalopelvic disproportion in primigravidae - Archana, R.; Patra, Sharda (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: Cephalopelvic disproportion (CPD) is associated with significant maternal and fetal morbidity and mortality in developing countries. CPD complicates 2-15% of pregnancies. This study aimed to determine the diagnostic accuracy of sacral rhomboid dimensions in the prediction of CPD in primigravidae Methods: This prospective study was conducted on 400 primigravidae at 37-week gestation in Department of Obstetrics and Gynaecology at Lady Hardinge Medical College, New Delhi. Women with height>145 cm were subjected to measurement of transverse and vertical diagonals (TD and VD) of sacral rhomboid prior to delivery. Following delivery, the women were divided in two groups: control group (normal delivery, n=290) and study group (caesarean section for CPD, n=56). The sacral rhomboid dimensions were compared in both the groups and statistically analysed. Results: The mean maternal height in both the groups showed no significant difference (156.88±5.7 vs 155.02±4.75, p=0.011). However, in univariate analysis, maternal height of≤154.5 cm, VD ≤10.25 cm and TD≤9.75 cm showed a diagnostic accuracy of 58.3%, 55.4% and 78%, respectively. Of all the parameters, TD≤9.75 cm was the most significant factor in predicting CPD (34% vs 13%), OR 3.3 (95%CI: 1.7- 6.7, p<0.001). Conclusions: A simple measurement of transverse diameter of sacral rhomboid is a better predictor of CPD in an average height Indian primigravidae. It can be used in community hospital to detect high risk primigravidae.